Land Conversion and Agrofuel Plantations in Mindanao: Promises and Uncertainties - (AFRIM), Alternate Forum for Research in Mindanao (Kasarinlan: Philippine Journal of Third World Studies; Vol 26 No 1-2 (2011): Food Sovereignty in Southeast Asia, 2012)
As a signatory to the Kyoto Protocol, the Philippines enacted the Biofuels Act of 2006 (RA 9367). Signed into law in January 2007, it aims for the phasing out of harmful gasoline additives and/or oxygenates, and the mandatory use of biofuels with one percent biodiesel blend and five percent bioethanol blend for all diesel and gasoline fuels, respectively. This policy has led to frenzied development of biofuel plantations, particularly sugarcane, cassava, and sweet sorghum for bioethanol production, and coconut, oil palm, and jatropha for production of biodiesel. Mindanao has been identified as a major contributor in fulfilling the Philippine government’s biofuel targets. The island’s vast agricultural lands are thus giving way to monocrop oil plantations.
Keywords: land conversion; Mindanao; biofuels; land grabbing